Historical Biogeography of Melanthiaceae: A Case of Out-of-North America Through the Bering Land Bridge - Kim, Changkyun; Kim, Sang-Chul; Kim, Joo-Hwan (Frontiers in Plant Science, 2019)
Intercontinental floristic disjunction between East Asia and North America in the Northern Hemisphere has received much attention during the past decades, but few studies have focused on the family level. Melanthiaceae, containing 196 species and 17 genera circumscribed in five tribes, is disjunctly distributed in Eurasia and North America. It is one of the excellent models for studying the evolution of biogeographic patterns in this region. Here, we present a fossil calibrated, molecular phylogeny of Melanthiaceae based on two chloroplast DNA datasets: one dataset includes extensive sampling (94 species representing all 17 genera of Melanthiaceae) of four chloroplast DNA regions (atpB, rbcL, matK, and ndhF) and the other includes six species representing all tribes of the the family for 78 coding genes of the chloroplast genome. Within these framework, we infer the historical biogeography of Melanthiaceae. Both datasets produce well resolved phylogenies of Melanthiaceae showing the monophyly of the family and the relationships among the five tribes. Melanthieae is found to be sister to the rest of the tribes of the family and the remaining taxa are divided into two major clades consisting of the Chionographideae + Heloniadeae clade and the Parideae + Xerophylleae clade. The molecular dating and the ancestral area analyses suggest that Melanthiaceae most likely originated in North America with its crown group dated at 92.1 mya in late Cretaceous. The favored ancestral areas at the crown lineages of tribes are also North America. In the family, seven independent migrations into East Asia from North America are inferred to have occurred in the Oligocene and the Miocene-Pliocene via historical paleo-land bridge connections. Cooling trends during the Oligocene resulted in the present East Asia-North America disjunct distribution, while the warm period during the middle Miocene and habitat heterogeneity stimulated diversification in East Asia. Our study provides the phylogenetic and biogeographical history of the Melanthiaceae and adds an example of ‘out of North America’ migration in the biogeographic history of the northern Hemisphere.